2020
DOI: 10.1002/cam4.2937
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative intensity‐modulated radiation therapy reduces local recurrence and improves overall survival in III‐N2 non‐small‐cell lung cancer: A single‐center, retrospective study

Abstract: Purpose:To determine the postoperative effects of radiotherapy (PORT) on the local recurrence-free survival (LRFS) and overall survival (OS) of stage III-N2 nonsmall-cell lung cancer (NSCLC). Materials and Methods: 183 patients with resected stage III-pN2 NSCLC from Hunan Cancer Hospital between 2013 and 2016 were divided into two groups for postoperative chemotherapy (POCT) (n = 105) or combination chemotherapy and radiotherapy (POCRT) (n = 78). The LRFS and OS were compared and the factors affecting local re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…The cumulative incidence of postoperative recurrence in the PORT group and non-PORT group, were generally comparable with recent studies (7,9,17,23). Furthermore, studies from our institution (7) and others (16,24) had reported a similar percentage of SCR among patients with recurrent disease (7.7-11.6% in the literature, 13.3% in our study). Compared with their counterpart, patients staged cN2 or ypN2 generally had a more advanced and aggressive disease, and thus it was reasonable for them to have a higher risk developing disease recurrence, including SCR (17,(25)(26)(27).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The cumulative incidence of postoperative recurrence in the PORT group and non-PORT group, were generally comparable with recent studies (7,9,17,23). Furthermore, studies from our institution (7) and others (16,24) had reported a similar percentage of SCR among patients with recurrent disease (7.7-11.6% in the literature, 13.3% in our study). Compared with their counterpart, patients staged cN2 or ypN2 generally had a more advanced and aggressive disease, and thus it was reasonable for them to have a higher risk developing disease recurrence, including SCR (17,(25)(26)(27).…”
Section: Discussionsupporting
confidence: 91%
“…The clinical value of PORT in completely resected (y)pN2 NSCLC was demonstrated again in our study, but the delineation of CTV remain controversial. In the current study, PORT significantly reduced LRR and improved OS1, which have been demonstrated in various studies ( 5 , 6 , 8 11 , 16 , 17 , 23 ). However, since ESRT was not routinely performed in our cancer institution ( 7 ), PORT failed to reduce SCR, indicating that the majority of SCRs represented the outgrowth of subclinical tumor lesions already in the supraclavicular region and were not originated from the loco-regional recurrent disease through lymphatic metastasis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The role of radiotherapy in patients with PSC is poorly defined (29). Radiotherapy has been used alone and in combination with chemotherapy in patients with unresectable disease or in an adjuvant setting for those with high rates of recurrence (30). Clinically, radiotherapy is always reserved for patients with rare types of lung cancer (31,32).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…These results made us more confident that patients who received PORT had a better survival rate. The reasons for this may be that PORT can eliminate regions of microscopic disease, and thus reduce locoregional recurrence and improve survival 16,29,30 . In addition, compared with older techniques that increased the risk of cardiac and pulmonary toxicity, more modern radiation techniques have become safer and bring a greater survival benefit for patients treated with PORT 8,31 …”
Section: Discussionmentioning
confidence: 99%